Improvement in health-related quality of life with recombinant factor IX prophylaxis in severe or moderately severe haemophilia B patients: results from the BAX326 Pivotal Study - Windyga, J.; Lin, V. W.; Epstein, J. D.; Ito, D.; Xiong, Y.; Abbuehl, B. E.; Ramirez, J. H. (Haemophilia : the official journal of the World Federation of Hemophilia, 2014)
Summary Little is known about the health‐related quality of life (HRQoL) burden of haemophilia B. The aim of this study was to assess HRQoL burden of haemophilia B, the benefit of recombinant factor IX (rFIX) prophylaxis and the HRQoL benefit of achieving a zero annual bleed rate. Subjects receiving rFIX (BAX326) prophylaxis or on‐demand completed the SF‐36 survey. Baseline SF‐36 scores were compared to the general US population scores to understand the HRQoL burden. Changes in SF‐36 scores between baseline and follow‐up were tested using t‐tests. Subgroup analysis was conducted to examine SF‐36 change among subjects who switched to BAX326 prophylaxis. SF‐36 scores were also compared between those with zero bleeds and those who bled during the study. Compared to the US norms, subjects reported lower average scores in all physical and several mental HRQoL domains. At follow‐up, prophylaxis subjects reported statistically significant and clinically meaningful improvements in overall physical HRQoL, as measured by the Physical Component Score (PCS) (mean change 2.60, P = 0.019), Bodily Pain (BP) (3.45, P = 0.015) and Role Physical (RP) domains (3.47, P = 0.016). Subjects who switched to prophylaxis from intermittent prophylaxis or on‐demand experienced more pronounced improvements not only in the PCS (3.21, P = 0.014), BP (3.71, P = 0.026), RP (4.43, P = 0.008) but also in Vitality (3.71, P = 0.04), Social Functioning (5.06, P = 0.002) and General Health domains (3.40, P = 0.009). Subjects achieving zero bleeds reported lower BP (P = 0.038). Prophylaxis with BAX326 significantly improved HRQoL in patients with moderately severe or severe haemophilia B by reducing bleeds.